Pengembangan Instrument Test untuk Mengukur HOTS Siswa pada Materi Asam Basa: Penelitian - Lara Juni Ulpa; M. Naswir; Fuldiaratman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Higher Order Thinking Skills (HOTS) are important competencies in 21st century learning, especially in chemistry that is conceptual and analytical. HOTS includes three levels of the revised Bloom's Taxonomy: analyzing (C4), evaluating (C5), and creating (C6), with creating as the highest level that demands creativity and original solutions. Acid-base material in grade XI is often considered abstract and difficult to understand, so an evaluation instrument is needed that can measure HOTS in a valid and reliable manner. This study aims to develop an electronic-based descriptive test instrument to measure students' HOTS. The development model is modified from the Wilson, Oriondo, and Antonio model, through three stages: design, limited testing, and measurement. The validation results by material experts (91%), construct (90%), and language (89%) show a very high category. The reliability test produced a coefficient of 0.87, indicating very good consistency. The discriminatory power of the questions is mostly good with a moderate level of difficulty. Teachers' assessment of the instrument's feasibility was 92%, and students' responses were 88%, both of which were categorized as very good. Thus, this instrument is suitable for measuring and improving students' HOTS in acid-base learning according to the Merdeka Curriculum.